Sketching : drawing techniques for product designers. - Eissen, Koos, ....-; Steur, Roselien, ....- (Amsterdam : Bis, 2007)
1. Side view sketches 2. Perspective drawing 3. Simplifyin shape 4. Elementary geometrical shapes 5. Special attention for ellipses 6. Rounding 7. Cross sections 8. Ideation 9. Explanatory drawings 10. Surface and textures 11. Emitting light 12. Context Are designers still making drawings by hand? Isn't it more advanced to use a computer in this computer era? Some may think sketching <http://www.sketching.nl > is a disappearing skill, but if you ever enter a design studio, you will find out differently. Studios still make sketches and drawings by hand and in most cases, quite a lot of them. They are an integral part of the decision-making process, used in the early stages of design, in brainstorming sessions, in the phase of research and concept exploration, and in presentation. Drawing has proved to be, next to verbal explanation, a powerful tool for communicating not only with fellow designers, engineers or model makers but also with clients, contractors and public offices. This book can be regarded as a standard book on design sketching, useful for students in product design.
Keywords: Tekenen